Product Differentiation in Auditing: Auditor Choice in the Market for Unseasoned New Issues (Book). - Williams, David D. (The Accounting Review, 1989)
Reviews the book "Product Differentiation in Auditing: Auditor Choice in the Market for Unseasoned New Issues," by Dan A. Simunic and Michael T. Stein.